Titanium and Cobalt Bimetallic Radical Redox Relay for the Isomerization of N-Bz Aziridines to Allylic Amides - Wood, Devin P.; Guan, Weiyang; Lin, Song (Synthesis, 2021)
Herein a bimetallic radical redox-relay strategy is employed to generate alkyl radicals under mild conditions with titanium(III) catalysis and terminated via hydrogen atom transfer with cobalt(II) catalysis to enact base-free isomerizations of N-Bz aziridines to N-Bz allylic amides. This reaction provides an alternative strategy for the synthesis of allylic amides from alkenes via a three-step sequence to accomplish a formal transpositional allylic amination.
Keywords: radical redox relay; titanium catalysis; cobalt catalysis; bimetallic; aziridines; allylic amines; allylic amides